Kajian Etnososiologi Jawa pada Sastra Anak di Antologi Anak “Meong Lan Arimong" (Sutasoma : Jurnal Sastra Jawa, 2023)
Children's literature will be the main attraction for children to learn about their culture. This study aims to describe: (1) socio-cultural relations; (2) the process of learning culture includes internalization, socialization, and enculturation contained in the anthology of children's stories "Meong lan Arimong". This research is classified as qualitative research with a qualitative descriptive method. The contents of children's stories are discussed using Javanese ethnosociology in the form of social and cultural relations of Javanese families and the process of learning one's own culture. The data used in this research are words, phrases, sentences, and discourses that contain socio-cultural relations, the process of learning culture itself includes internalization, socialization, and enculturation. The data source used is an anthology of children's stories “Meong lan Arimong. The research subjects were taken using purposive sampling. The data collection technique uses document analysis techniques, while the data analysis techniques use interactive analysis techniques. Based on the results of the analysis that has been carried out on the seven selected Jaya Baya magazine crikaks, all of them have: (1) socio-cultural relations caused by the existence of Javanese culture which is raised in each children's story; (2) the process of learning culture itself includes internalization, socialization, and enculturation experienced by the main character and the most prominent socialization process is obtained because it is in that process that reciprocal interactions occur. Keywords: ethnosociology; childrens stories; children's literature; meong lan arimon